What a drag it is getting old? Mental health and loneliness beyond age 50 - Jan van Ours (Tinbergen Institute, 2020)
This paper studies mental health and loneliness in the Netherlands for individuals beyond age 50. The analysis is based on panel data over the period 2008 to 2018 and focuses on the effects of life events and aging. It appears that mental health gets worse and loneliness increases if individuals lose their partner or become unemployed. On average, mental health of males and high educated females improves at retirement. With respect to aging, the main conclusions are that mental health improves while loneliness goes down at least up to the high 70s. From the perspective of mental health and loneliness it does not seem to be a drag getting old.
Keywords: I31; J14; 330; mental health; loneliness; age; old people